NASIONALISME, KETAHANAN NASIONAL, DAN KETAHANAN REGIONAL - Armawi, Armaidy (PKn Progresif, 2008)
The New Order fall down a crash  by the reform movement in 1998 to open the slabs for the new nation of Indonesia. Where is the era of the freedom of people participating is wide open. However, on the other hand, the fact euforia reforms raise new problems, some areas where demand independence. This, if left alone will endanger the national and regional resilience. But back to foster a sense of nationalism in this nation a duty to maintain the unity and the unity of the nation.